2018
DOI: 10.3389/fmicb.2018.02888
|View full text |Cite
|
Sign up to set email alerts
|

Carbapenem-Resistant Enterobacteriaceae Infections: Taiwan Aspects

Abstract: Carbapenem-resistant Enterobacteriaceae (CRE), a major resistance concern emerging during the last decade because of significantly compromising the efficacy of carbapenem agents, has currently become an important focus of infection control. Many investigations have shown a high association of CRE infections with high case-fatality rates. In Taiwan, a few surveys observed that a significant proportion (29–47%) of the CR-Klebsiella pneumoniae isolates harbored a plasmidic allele encoding K. pneumoniae carbapenem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
32
2
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 47 publications
(36 citation statements)
references
References 78 publications
1
32
2
1
Order By: Relevance
“…One study from India reported no urine colonization of imipenem-or meropenem-resistant Enterobacteriaceae in 433 healthy individuals (Lohiya et al, 2015). In our study, we did not find VRE or CRE colonization among healthy adults, despite the increased prevalence of both pathogens in hospitals in Taiwan (Wang et al, 2013;Jean et al, 2018). Our results suggest that in the community, the spread of VRE or CRE occurs mainly in health care facilities such as nursing homes (Lee et al, 2017).…”
Section: Discussioncontrasting
confidence: 53%
“…One study from India reported no urine colonization of imipenem-or meropenem-resistant Enterobacteriaceae in 433 healthy individuals (Lohiya et al, 2015). In our study, we did not find VRE or CRE colonization among healthy adults, despite the increased prevalence of both pathogens in hospitals in Taiwan (Wang et al, 2013;Jean et al, 2018). Our results suggest that in the community, the spread of VRE or CRE occurs mainly in health care facilities such as nursing homes (Lee et al, 2017).…”
Section: Discussioncontrasting
confidence: 53%
“…The increase in CRE is a serious matter due to high case-fatality rates (>30%). [24][25][26] Studying the mechanisms of CRE is an essential step in planning a national public health strategy for this emerging pathogen. 27 Several studies have been studied the mechanisms of resistance to carbapenem in CRE isolates from Iran.…”
Section: Discussionmentioning
confidence: 99%
“…Carbapenems are often considered last resort antibiotics in the treatment of infections due to multidrug-resistant Enterobacteriaceae clinical isolates, since they are stable even in response to extended-spectrum b-lactamases (ESBLs) and AmpC enzymes (Tsakris et al 2010;Jean et al 2018;Carrasco-Anabal on et al 2019;Wang et al 2019). However, the carbapenem resistance has been increasingly reported among Enterobacteriaceae in the past few years, which is largely attributed to the production of metallo-b-lactamases (MBLs), KPC and OXA-48 (Yusuf et al 2014;Tijet et al 2016;No€ el et al 2017;Tamma and Simner 2018).…”
Section: Introductionmentioning
confidence: 99%